Exacerbation of non‐steroidal anti‐inflammatory drug‐induced enteropathy in C‐C chemokine receptor type 7‐deficient mice. Issue 8 (28th April 2022) - Yamaguchi, Toshio; Iijima, Hideki; Yoshihara, Takeo; Tani, Mizuki; Otake, Yuriko; Iwatani, Shuko; Amano, Takahiro; Tashiro, Taku; Kurahashi, Tomohide; Inoue, Takanori; Tsujii, Yoshiki; Hayashi, Yoshito; et al.
Abstract: Background and Aim: Non‐steroidal anti‐inflammatory drugs (NSAIDs) induce intestinal enteropathy and the pathophysiology is related to immune‐mediated mechanisms. We aimed to investigate the role of C‐C chemokine receptor type 7 (CCR7) which regulates immune cell migration in NSAID‐induced enteropathy. Methods: Injury of the small intestine was evaluated 24 h after the subcutaneous injection of indomethacin in CCR7‐deficient ( Ccr7 −/− ) and wild‐type (WT) mice. The cellular profile and cytokine production in intestinal cells were analyzed. Indomethacin‐induced enteropathy was evaluated in mice adoptively transferred with CD103 + dendritic cells (DCs) from Ccr7 −/− or WT mice. Results: Indomethacin induced more severe intestinal injury in Ccr7 −/− mice than in WT mice. The major inflammatory cytokines were not increased and the proportion of regulatory T cells following indomethacin injection was not decreased in Ccr7 −/− mice compared with WT mice. The expression of interleukin (IL)‐22 binding protein (IL‐22BP), which inhibits IL‐22 activity, was significantly higher in CD103 + DCs from Ccr7 −/− mice than those from WT mice. Mice adoptively transferred with CD103 + DCs isolated from Ccr7 −/− mice exhibited more severe intestinal injury following indomethacin injection compared with those adoptively transferred with CD103 + DCs of WT mice. Ccr7 −/− mice injected with indomethacin showed a significant reduction in regenerating islet‐derived 1 ( Reg1 ) mRNA expression, which is regulated by IL‐22, in intestinal epithelial cells. Conclusions: C‐C chemokine receptor type 7 deficiency exacerbated NSAID‐induced enteropathy in association with an altered phenotype of CD103 + DCs that produces IL‐22BP. CCR7 contributes to protect the small intestine from NSAID‐induced mucosal injury.